Prunelle Deleville, Métamorphose des Métamorphoses, édition critique et étude littéraire des manuscrits Z de l’Ovide moralisé - Prunelle Deleville (Perspectives Médiévales)
Among the late copies of the Ovide moralisé, a specific group, called Z, provides a true rewriting of the original work. It consists of the codices: Bern, Burgerbibliothek, 10 (Z1) written after 1456 ; Paris, BnF, French 874 (Z2) copied in 1456 ; Paris, BnF, French 870 (Z3) composed around 1400 for the text and 1450 for the decoration ; Paris, BnF, French 19121 (Z4) probably made between 1390 and 1410. The rewriter modifies the story of the fable, adds historical expositions unheard of in the tradition of the Ovide moralisé. These are the common modifications found in the Z copies. However, there are divergences in this family. The Z3 and Z4 witnesses are devoid of religious allegories, whereas these have been reintroduced in Z1 and Z2. These four manuscripts thus present a rich moment in the life of the Ovide moralisé. The edition of this text, according to manuscript Z3, takes into account the linguistic specificities of this reworking of the Ovide moralisé a century after its creation, but also the literary aspects of this rewriting. The reworking Z, which corresponds to the text of subset Z34, is coherent and thoughtful. Traces of Christian dogma are meticulously erased. The aesthetics of the text converges with that of the prose settings that multiplied at the time from the end of the 14th century onwards, but above all with the literary debates of the time, such as that around the Roman de la Rose. The reviser also expresses the fact that his rejection of allegories is based on a stricter adequacy with Ovid, who could not conceive of Christianizing interpretations of his own text.